Magnetohydrodynamic flow of carbon nanotubes blood based hybrid nanofluids with the impact of thermal radiation over a permeable surface - Rehman, Ali; İnç, Mustafa; Chou, Dean (Elsevier, 2025)
This study looks at the magnetohydrodynamic (MHD) flow properties of blood-based hybrid nanofluids (HNFs) containing carbon nanotubes (CNTs), such as SWCNTs and MWCNTs with multiple walls. Thermal radiation is present during the study. The study is mostly about how these fluids behave on a permeable surface in steadystate laminar flow. To make things easier, boundary layer (BL) approximations are used to simplify and solve the equations for momentum and energy. We transform these equations into a system of nonlinear ODEs via similarity transformations (STs) and solve them semi-numerically. This study looks at how surface permeability, magnetic field (MF) strength, and thermal radiation affect the flow and heat transfer properties of fluids. It does this by looking closely at key parameters like the permeability parameter, the radiation parameter, the power law index, the CSP, the nanoparticle volume fraction (VF), the heat generation, the Eckert number (EN), and the MF strength. The results, which are shown in the form of graphs and a table with the NN and skin friction (SF) coefficients, give us important information about how blood-based (BB) HNFs with CNTs behave in MHD conditions. The moment of HNF particles decreases as the magnetic parameter (MP), CSP, and nanoparticle volume friction all go up. However, this has the opposite effect on the temperature profile as the EN, radiation parameter, heat generation parameter, and nanoparticle volume friction all go up. This study shows how important permeability and thermal radiation are in changing these dynamics. It also helps to create better ways to control temperature in engineering and biomedical settings.
Keywords: Stretching surface; Homotopy analysis method (HAM); Carbon nanotubes; Viscous dissipation